2021
DOI: 10.1039/d0ra09564h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ±σ-hole and ±R˙-hole interactions formed by tetrel-containing complexes: a computational study

Abstract: The characteristics and nature of ±R˙-hole interactions were uncovered for the first time and compared to their ±σ-hole analogs in ˙TF3⋯ and W–T–F3⋯B/R˙/A complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…The Point-of-charge (PoC) approach was documented as an informative tool for elucidating the electrostatic inclination of the group III-VIII element-containing molecules to participate in noncovalent interactions [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. With the help of the PoC approach, negatively and positively charged points were utilized to parody the nucleophilic and electrophilic effects on the inspected molecular systems, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Point-of-charge (PoC) approach was documented as an informative tool for elucidating the electrostatic inclination of the group III-VIII element-containing molecules to participate in noncovalent interactions [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. With the help of the PoC approach, negatively and positively charged points were utilized to parody the nucleophilic and electrophilic effects on the inspected molecular systems, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, all the inspected halogen-containing molecules showed a propensity to participate in type I–IV halogen⋯halogen interactions. Clearly, the energetic features outlined that the highest binding energy was discerned to type II interactions, which is inconsistent with the chalcogen⋯chalcogen analogs that announced the preference of type IV interactions [ 53 ]. On the other hand, the lowest E binding was relevant to type III interactions synchronically to chalcogen⋯chalcogen counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…was implemented for the MEP calculations in accord with previous recommendations that confirmed its valuable description for the surface of chemical systems. 62 With the support of the point-of-charge (PoC) approach, a purely electrostatic model for chalcogen-based interactions was established using negatively-and positively-charged points with a value of AE0.50 a.u., which were dedicated to Lewis base and acid mimics, [63][64][65][66] respectively. In addition, the YÁ Á ÁPoC distance effect was systematically elucidated in the range from 2.5 to 6.0 Å along the x-axis (i.e., the outer equatorial surface of the chalcogen atom) and z-axis (i.e., the axial portion of the chalcogen atom) with +C = YÁ Á ÁPoC angles of 1801 and 901, respectively (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A point-of-charge (PoC) approach was recently documented as an informative tool to thoroughly study the s-, p-, lone-pair (lp)-, and radical (R )-hole interactions from an electrostatic perspective, with the utilization of negative and positive PoCs mimicking the roles of Lewis base and acid, respectively. 66,[84][85][86][87][88][89] With the implementation of PoC calculations, molecular stabilization energies (E stabilization ) of YQ Q QCQ Q QYÁ Á ÁPoC systems were calculated using AE0.50 a.u. PoCs at YÁ Á ÁPoC distances in the range of 2.5-6.0 Å along the x-axis and z-axis with +CQ Q QYÁ Á ÁPoC angles of 1801 and 901, respectively (see the Computational methods section for details).…”
Section: Point-of-charge (Poc) Calculationsmentioning
confidence: 99%
“…In a series of studies, the covalently bonded atoms of group IV–VII were reported with recognizable ability to form regions of depletion in electron density, 9 12 dubbed as σ-, 13 π-, 14 lone-pair (lp)-, 15 and radical (R • )-holes. 16 The holes of group IV–VII element-containing molecules can interact with Lewis bases, forming tetrel, 17 19 pnicogen, 20 25 chalcogen, 26 31 and halogen 13 , 31 36 bonds, respectively. Among hole-bonding complexes, the interactions of pnicogen-containing molecules with Lewis bases have found sustained attention of a variety of theoretical 37 42 and experimental studies 43 45 by dint of their significant importance in chemical reactions 46 48 and biological systems.…”
Section: Introductionmentioning
confidence: 99%